Multimodal element (including lithium) mapping in a Mg-9Li-4Al-1Zn alloy - Yu Zhang; Yang Liu; Zhuoran Zeng; Nick Birbilis; Philip N.H. Nakashima; Laure Bourgeois (Journal of Magnesium and Alloys)
Determining the distribution of alloying elements, particularly lithium, is crucial for a holistic understanding of magnesium-lithium-based alloys. In this work, a bespoke ratio spectrum-imaging method based on electron energy-loss spectroscopy, in combination with time-of-flight secondary ion mass spectrometry, energy-dispersive X-ray spectroscopy and Z-contrast imaging, was applied to an as-rolled LAZ941 alloy (Mg-9Li-4Al-1Zn in wt.%). This was done to characterize the distribution of alloying elements, including the distribution of solute in the magnesium matrix. The applications of different mapping techniques revealed that precipitates with two different morphologies are rich in Li, Al and Zn, compared to their surrounding matrix. Additionally, it was confirmed that the β-phase of the alloy contains higher Li and lower Mg concentrations when compared to the α-phase. This study demonstrated the effectiveness and accuracy of the ratio spectrum-imaging method for mapping the elemental distribution (including lithium) in a range of Li-containing materials.